YOUTH ENTREPRENEURSHIP AND POVERTY REDUCTION IN ORLU LOCAL GOVERNMENT AREA, IMO STATE, NIGERIA - Nwachukwu, Chinweotito Joy; Osita-Njoku, Agnes (African Journal of Social and Behavioural Sciences, 2024)
This study focused on youth entrepreneurship and poverty reduction in Orlu Local Government Area of Imo State, Nigeria. The objective of the study is to examine the effect of entrepreneurial skill acquisition and poverty reduction among youth in Orlu LGA. Using a sample size of 384 respondents, determined through the margin of error formula for an unknown population, eight communities within Orlu LGA were randomly selected. Fortyeight youths actively involved in entrepreneurial ventures were sampled from each of the selected communities. The study utilized a survey research design, chosen for its adaptability in data collection, making it ideal for a quantitative approach. Data were primarily collected through questionnaires distributed to the participating youth and analysed with pie charts, bar charts, and chi-square tests. The study hypothesized a significant correlation between entrepreneurship training/mentorship and the acquisition of entrepreneurial skills among Orlu's youth. The results indicated a notable association between access to such training/mentorship and the youths' entrepreneurial skill acquisition. Based on these outcomes, recommendations included forming partnerships with seasoned entrepreneurs, industry professionals, and local business leaders to provide mentorship that could address the specific challenges of young entrepreneurs. Furthermore, it was suggested to enhance entrepreneurship training and mentorship programs to ensure they are accessible to youth across all communities in Orlu LGA. Additionally, establishing micro-finance programs or grant schemes aimed at supporting young entrepreneurs in Orlu LGA would boost their training participation and facilitate their entry into various business ventures.